XFEM for fracture analysis of functionally graded structures - Kumar, M.R. Nanda; Mahajan, Akshay D; Murthy, A. Ramachandra; Gopinath, Smitha; Iyer, Nagesh R (Journal of Structural Engineering, 2025)
This paper presents the development of methodologies in Extended Finite Element Method (XFEM) framework for the fracture analysis of functionally graded structural panels. The main focus is on accurate computation of Stress Intensity Factor (SIF) using XFEM in a cracked Functionally Graded Material (FGM) panels. XFEM formulations for FGM such as crack modelling, element stiffness matrix formulation and numerical integration are presented in detail. XFEM solutions are used to compute the Stress Intensity Factor using domain form of interaction integral with incompatible auxiliary strain field. XFEM formulations are implemented in MATLAB code as well as modelled using XFEM module of ABAQUS software to compute SIF of cracked FGM panels. Numerical studies are carried out on cracked FGM panels and computed SIF from MATLAB and ABAQUS software are compared with the correspondingsolutions available in the literature and are found to be in very good agreement.